Disability Law Reform in Indonesia: Analyzing Policy Gap Implementation in Kudus Regency - Dewi, Siti Malaiha; Qodarsasi, Umi; Sally, Novian Uticha; Syamsudin, Muhammad Hasan; Maskur, Muhammad Azil (Universitas Negeri Semarang, 2025)
Regional Regulation Number 10 of 2021 on the Protection and Fulfillment of the Rights of Persons with Disabilities in Kudus City is a hope for the realization of an inclusive city. The number of people with disabilities in Kudus City reaches 0.5% of the total population of Kudus. Still, data in the field reveal that implementing the Disability Regional Regulation in Kudus faces significant implementation barriers. This study examines legal reforms that can be carried out by focusing on complementing the shortcomings of previous studies, which more often portrayed the success of the implementation of the Regional Regulation and disregarded the aspects of obstacles and barriers in the implementation process. In addition, this study analyzes the failure of implementing the Disability Regional Regulation and the factors causing it. The design of this study is qualitative, where data collection was performed through interviews, online sources, and reports. The leading theory used in this study is the implementation of policies from George C. Edward III. The findings of this study stated that four variables must be re-evaluated in implementing the Disability Regional Regulation in Kudus, including communication, resources, disposition, and bureaucratic structure. The results of this study include a recommendation for the regional government to promptly enact the Regent Regulation (Perbup) so that the goals of protecting and fulfilling the rights of persons with disabilities can be achieved without further delay.